2022
DOI: 10.1007/s11306-022-01925-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic changes in cats with renal disease and calcium oxalate uroliths

Abstract: Introduction There is a significant incidence of cats with renal disease (RD) and calcium oxalate (CaOx) kidney uroliths in domesticated cats. Foods which aid in the management of these diseases may be enhanced through understanding the underlying metabolomic changes. Objective Assess the metabolomic profile with a view to identifying metabolomic targets which could aid in the management of renal disease and CaOx uroliths. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Although these lipid metabolites were only weakly-correlated with clinical and laboratory parameters (Supplementary File 3), the roles that lipid metabolism plays in CKD, especially in its progression from early-stage to late-stage disease, are largely unknown 26 , 28 , such that their levels in serum may increase or decrease via mechanisms that are not proportionate to conventional monitoring parameters. Similar to this study, robust changes to lipid metabolism were identified in the plasma metabolome of purpose-bred research cats by both Hall et aland Jewel et al, where cats with CKD showed alterations to multiple fatty acids including phospholipids, ceramides, and dicarboxylates when compared to healthy cats 9 , 10 . In turn, both increases and decreases in serum lipid metabolites should be considered as biologically meaningful changes in cats with CKD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although these lipid metabolites were only weakly-correlated with clinical and laboratory parameters (Supplementary File 3), the roles that lipid metabolism plays in CKD, especially in its progression from early-stage to late-stage disease, are largely unknown 26 , 28 , such that their levels in serum may increase or decrease via mechanisms that are not proportionate to conventional monitoring parameters. Similar to this study, robust changes to lipid metabolism were identified in the plasma metabolome of purpose-bred research cats by both Hall et aland Jewel et al, where cats with CKD showed alterations to multiple fatty acids including phospholipids, ceramides, and dicarboxylates when compared to healthy cats 9 , 10 . In turn, both increases and decreases in serum lipid metabolites should be considered as biologically meaningful changes in cats with CKD.…”
Section: Discussionsupporting
confidence: 82%
“…Various feline untargeted metabolomics studies have been performed 8 12 . The studies used plasma 9 , 10 , serum 11 , feces 8 , 9 , and urine 12 collected from cats with early-stage CKD. Most studies used purpose-bred research cats 8 11 and examined dietary impacts on the metabolome 8 , 9 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 78 ], it is now necessary to consider that urinary bacteria are also involved in the formation of calcium oxalate stones, with the exact mechanism yet to be elucidated. The urinary microbiota could act by altering the urine pH, producing metabolites that influence the solubility of minerals in the urine, interacting with substances like citrate that inhibit stone formation, increasing oxalate concentration, or serving as nuclei for mineral crystallization [ 22 , 31 , 64 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…This method has been extensively performed in people with CKD and was successfully used for biomarker discovery for early diagnosis and etiology identi cation [7]. Various feline untargeted metabolomics studies have been performed [8][9][10][11][12]. The studies used plasma [9,10], serum [11], feces [8,9], and urine [12] collected from cats with early-stage CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Various feline untargeted metabolomics studies have been performed [8][9][10][11][12]. The studies used plasma [9,10], serum [11], feces [8,9], and urine [12] collected from cats with early-stage CKD. Most studies used purpose-bred research cats [8][9][10][11] and examined dietary impacts on the metabolome [8, 9,11].…”
Section: Introductionmentioning
confidence: 99%